Flexible and transparent films produced from cellulose nanowhisker reinforced agarose - Felfel, Reda M.; Hossain, Kazi M. Zakir; Kabir, Sumaya F.; Yee, Soon L.; Ahmed, Ifty; Grant, David M. (Elsevier, 2018)
Transparent and flexible nanocomposite films with a range of Agarose to Cellulose Nano-Whisker (CNW) ratios were produced using never-dried CNWs. The incorporation of never-dried CNWs within Agarose played an important role in the surface roughness (Ra 7–15 nm) and light transparency of the films (from 84 to 90%). Surface induced crystallisation of Agarose by CNWs was also found with increasing percentage of crystallinity (up to 79%) for the nanocomposite films, where CNW acted as nucleating sites. The enhanced tensile strength (ca. 30% increase) and modulus (ca. 90% increase) properties of the nanocomposite films compared to the control Agarose film indicated the effectiveness of the nanowhiskers incorporation. The storage modulus of the nanocomposite films increased also to be tripled Agarose alone as the CNWs content reached 43%. The swelling kinetics of the nanocomposites revealed that addition of CNWs reduced the long-term swelling capacity and swelling rate of the nanocomposite.